IDENTIFYING THE POTENTIAL OF Saurauia vulcani Korth. LEAVES ON BLOOD GLUCOSE LEVEL, HISTOPATHOLOGY OF PANCREATIC AND SPLEEN IN RATS (Rattus norvegicus) INDUCED ALLOXAN – IN VIVO AND IN SILICO APPROACH - Erlintan Sinaga; Uswatun Hasanah; Feimmy Ruth Pratiwi Sipahutar; Hudson Sidabutar; Melati Nugrahalia Sipahutar (JBIO: jurnal biosains (the journal of biosciences), 2023)
Insulin resistance related to pancreatic islet and spleen was one of incidence for diabetes mellitus disease. Our study determined the potential antidiabetic of Pirdot leaves (Saurauia vulcani, Korth.) (EEP) through in vivo and in silico approach. The effect of Pirdot on blood glucose level and histopathological pancreatic and spleen was analyzed by in vivo. Thirty male Wistar rats were divided into five groups as follows. Group KN served as negative control and was orally given distilled water; group KP were only 5.04 mg/ kg alloxan administered; group P1 were administered 16.5 mg/kg EEP and 5.04 mg/kg alloxan; group P2 were administered 33 mg/kg EEP and 5.04 mg/kg alloxan; group P3 rats 66 mg/kg EEP and 5.04 mg/kg alloxan. A single dose of alloxan was given in rats diabetic at KP, P1, P2, and P3 group treatment. Furthermore, the protein-protein interaction (PPI) and molecular docking were used to predict the interaction between the crossed genes in diabetes mellitus (DM) with 6 active compounds of Pirdot through in silico approach. The results indicated that Saurauia vulcani significantly decreased blood glucose and improved the histopathological alteration of pancreatic islet and spleen in alloxan induced treated diabetic rats. Moreover, the network pharmacology demonstrated ten hub genes and three genes target such as GANC (α-glucosidase), DPP4, and PTPN1 (tyrosine phosphatase protein) contributed in DM signaling pathway. Finally, the molecular docking study showed that the bioactive compounds Pirdot have a good binding affinity to the active site of PTP1B and α-glucosidase protein when compared to acarbose as a control compound